European monetary union and national labour markets - Peter Rühmann (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 1999)
When a nation joins EMU it relinquishes monetary policy tools and its economy becomes more and more exposed to international competition. This has provoked (sometimes quite opposing) fears concerning the future of "Euroland". With respect to the labour markets of the EMU-zone some authors expect a catching-up of wages irrespectively of differences in productivity while others are suspicious of a process of competitive underbidding. Before addressing this controversy in chapter 4, the changes will be described that are relevant for the labour markets' participants and that have been brought about by the start of EMU. Since the beginning of this year the member states of the European Monetary Union no longer have at their disposal the instruments of monetary policy or the ability to adjust exchange rates. Further, the Stability and Growth Pact restrains their fiscal autonomy. The second chapter of this paper contains some general considerations of the consequences that may result from this fundamental change in the conduct of economic policy. At the same time, EMU probably will intensify the process of transnational economic integration and, thus, may further diminish the manoeuvrability of the member states. In the third chapter we will look at the effects of this development on the national labour markets in some detail. It is certainly not clear how the participants in the labour markets will respond to the important changes in the environment in which they operate. Some of the alternatives that have been discussed particularly in Germany, will be presented in the fourth chapter.
Keywords: 330